A rare case of adult Wilms tumor: case report and literature review from a tertiary centre - Trivedi, Sameer; Reddy, K. Shridhar; Yadav, Mahima; Agrawal, Lalit Kumar; Kumar, Ujwal; Singh, Yashasvi (International Surgery Journal, 2021)
Nephroblastoma (Wilms’ tumour) in adult population is extremely rarefied scenario and has a poorer prognosis than paediatric Wilms’ tumour with an incidence of about 0.2 per million per year in the USA and Europe. Clinical presentation is also distinct between children and adults. In adults, manifestation is usually hematuria and abdominal pain while paediatric cases frequently present with an asymptomatic abdominal lump. It is arduous to demarcate adult Wilms’ tumour from renal cell carcinoma based on radiology alone. The final diagnosis in adult cases is often fortuitous following radical nephrectomy for presumed adult Renal cell carcinoma (RCC). Due to the lack of published discussion, there are no standard protocols for the management of adult Wilms tumour (WT) hence it is managed as per paediatric WT. In view of this, we report a case of adult WT in a 32-years-old female, who was diagnosed propitiously following right radical nephrectomy for an assumed right renal mass.